Assessment of Nelumbo nucifera and Hydrilla verticillata in the treatment of pharmaceutical industry effluent from 24 Parganas, West Bengal - Shamba Chatterjee (Chemical Engineering Diponegoro University, 2014)
Modern day technologies employed in industrialization and unhygienic lifestyle of mankind has led to a severe environmental menace resulting in pollution of freshwater bodies. Pharmaceutical industry effluents cause eutrophication and provide adequate nutrients for growth of pathogenic bacteria. This study has been conducted with aquatic plants water lotus (Nelumbo nucifera) and hydrilla (Hydrilla verticillata) with an novel aim to treat pharmaceutical industry effluents showing the outcome of the experiments carried out with the effluents collected from rural areas of 24 Parganas, West Bengal, India. Determination of pH, solid suspend, BOD5, NH3-N, MPN and coliform test were used for this notioned purpose. Pharmaceutical waste effluent water treated with water lotus showed less pH, solid suspend, DO, BOD, NH3-N, MPN and coliform bacteria than hydrilla treatment when compared to the control. In conclusion, water lotus is found to be more efficient in treatment of pharmaceutical industry effluent waste water than hydrilla.